Effects of Private Tuition on the Academic Achievement of Secondary School Students in Subject of Mathematics in Kohat Division, Pakistan - Qaiser Suleman; Ishtiaq Hussain (Journal of Education and Learning (EduLearn), 2014)
Research reveals that private or home tuition after school time plays a crucial role in strengthening and improving studentâ€™s academic achievement. The purpose of the study was to explore the effects of private tuition on the academic achievement of students in subject of mathematics at secondary school level. All the students at secondary school level in Kohat Division (Pakistan) constituted the population of the study. The study was delimited to the students of Government High School Ahmadi Banda Karak only. Fifty students of class 09 were selected as sample of the study. Sample students were divided into two groups i.e. control group and experimental group by equating them on the basis of their previous knowledge in subject of mathematics as determined through a pre-test. Each group was composed of 25 students. Students of the experimental group were engaged in tuition for two hours after school time. The study was experimental in nature therefore, â€œThe pre-test-post-test Equivalent Groups Designâ€ was used for the collection of data. Statistical tools i.e. the mean, standard deviation and differences of means were computed for each group. Significance of difference between the mean scores of both the experimental and control groups on the variable of pre-test and post test scores was tested at 0.05 levels by applying t-test. After statistical analysis of the data, the researchers concluded that there is significant positive effect of private tuition on the academic achievement of students in subject of mathematics at secondary school level. Based on the findings, it was recommended that parents should arrange private tuition for their children to move up their achievement level in subject of mathematics.